2010
DOI: 10.1161/circresaha.110.232470
|View full text |Cite
|
Sign up to set email alerts
|

A Major Role for hERG in Determining Frequency of Reentry in Neonatal Rat Ventricular Myocyte Monolayer

Abstract: Rationale:The rapid delayed rectifier potassium current, I Kr , which flows through the human ether-a-go-gorelated (hERG) channel, is a major determinant of the shape and duration of the human cardiac action potential (APD). However, it is unknown whether the time dependency of I Kr enables it to control APD, conduction velocity (CV), and wavelength (WL) at the exceedingly high activation frequencies that are relevant to cardiac reentry and fibrillation.Objective: To test the hypothesis that upregulation of hE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 45 publications
(57 citation statements)
references
References 28 publications
(29 reference statements)
3
53
0
1
Order By: Relevance
“…As in previous studies (22,34,50), the choice of the two-dimensional tissue geometry avoids confounding interpretation of the ionic mechanisms with added complexities such as structural and electrophysiological heterogeneities. A planar wavefront was initiated by a stimulus applied at the lower tissue edge, followed by another stimulus applied on a square area in the tissue bottom-left corner at a CI within the vulnerable window.…”
Section: Methodsmentioning
confidence: 99%
“…As in previous studies (22,34,50), the choice of the two-dimensional tissue geometry avoids confounding interpretation of the ionic mechanisms with added complexities such as structural and electrophysiological heterogeneities. A planar wavefront was initiated by a stimulus applied at the lower tissue edge, followed by another stimulus applied on a square area in the tissue bottom-left corner at a CI within the vulnerable window.…”
Section: Methodsmentioning
confidence: 99%
“…the fast and the slow delayed rectifier K + currents, viz. I Kr and I Ks [44], we utilized monolayers of confluent, electrically coupled neonatal rat ventricular myocytes (NRVMs) [45,46]. The density of either I Ks or I Kr was increased by adenoviral overexpression of either KvLQT1-minK, or hERG, respectively in NRVM monolayers.…”
Section: Spiral Waves: Ionic Bases Of Initiation and Maintenancementioning
confidence: 99%
“…Experiments in isolated HEK cells and suggested that the increased wavebreaks was because of the phenomenon of post-repolarization refractoriness, occurring due to residual outward I Ks current, following the action potential [45]. In contrast to I Ks , a larger density of I Kr caused the spiral to accelerate significantly compared to control (∼21 Hz in the former, versus ∼9 Hz in the latter case) [46]. Both experiments and simulations showed that the faster spiral was due to APD shortening, as well as transient V rest hyperpolarization, which again would indirectly affect spiral frequency by modifying I Na availability [46].…”
Section: Spiral Waves: Ionic Bases Of Initiation and Maintenancementioning
confidence: 99%
“…First, we utilized primary cultures of neonatal rat cardiomyocyte monolayers. 25 We also measured contractility in monolayers of human embryonic stem cell-derived cardiomyocytes (hESC-CMs) that have been used to generate specific cardiac myocyte lineages 26,27 and approved on the NIH stem cell registry. 28,29 The human cardiac cell line used was a control or healthy stem cell derived cardiomyocyte, UM22-2.…”
Section: B Cultured Cardiomyocyte Monolayersmentioning
confidence: 99%